Sperm Protein Antigen 17 Expression Correlates With Lymph Node Metastasis and Worse Overall Survival in Patients With Breast Cancer - Zhou, Yu-ting; Qiu, Juan-juan; Wang, Yao; Liu, Peng-cheng; Lv, Qing; Du, Zheng-gui (Frontiers in Oncology, 2019)
Purpose: The expression and role of sperm protein antigen 17 (SPA17), which has been confirmed to be immunogenic, in breast cancer remain unclear. We examined the expression of SPA17 in breast cancer and assessed its effect on patient prognosis and its function in breast cancer development. Methods: SPA17 expression was evaluated by immunohistochemistry and Q-RT-PCR in 120 breast tissue samples. Correlation of SPA17 expression with the patients' clinicopathological parameters and overall survival was assessed. The function of SPA17 was also explored. Results: By reviewing Gene Expression Omnibus datasets, we found that SPA17 expression in ductal breast carcinoma in situ (log2[fold change] = 1.14, p-value = 0.004) and invasive ductal breast cancer (log2[fold change] = 1.03, p-value = 0.016) tissues was 2.20 and 2.05 times higher, respectively, than that in normal breast tissues. Our result also showed that 27% (27/100) of breast cancer samples expressed SPA17 but none of the normal breast (0/20) samples did. Lymph node metastasis (p < 0.001) and molecular subtyping (p = 0.002) were independent factors associated with SPA17 expression. Most importantly, SPA17 expression resulted in poor prognosis. In addition, cell function assay validated that SPA17 increased the migration (p < 0.001) and invasion (p = 0.007) of breast cancer cells, but not affected the proliferation of breast cancer cells. Conclusion: Our results demonstrated the vital role of SPA17 in the development and metastasis of breast cancer and that SPA17 may be a new therapeutic target in improving breast cancer prognosis.